2019
DOI: 10.1590/0100-5405/187147
|View full text |Cite
|
Sign up to set email alerts
|

Métodos de inoculação de Fusarium solani e Sclerotium rolfsii em meloeiro

Abstract: RESUMO A podridão-do-colo do meloeiro, causada por Fusarium solani (Mart.). e a murcha do Sclerotium, causada pelo patógeno Sclerotium rolfsii Sacc., são importantes doenças que acometem o meloeiro. Metodologias adequadas de inoculação destes patógenos nas culturas são de grande importância para diversos estudos envolvendo o controle destas doenças, como a resistência de acessos de meloeiro. Desta forma, este trabalho teve como objetivo determinar métodos de inoculação de F. solani e S. rolfsii em meloeiro, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
1
1
0
1
Order By: Relevance
“…The IAC 9453 isolate displayed higher virulence in both methods. Nogueira et al (2019) reported similar findings, noting that the inoculation method involving infested rice was more effective Semina: Ciênc. Agrár.…”
Section: Adjustment Of Inoculation Methods and Fungal Isolatessupporting
confidence: 55%
“…The IAC 9453 isolate displayed higher virulence in both methods. Nogueira et al (2019) reported similar findings, noting that the inoculation method involving infested rice was more effective Semina: Ciênc. Agrár.…”
Section: Adjustment Of Inoculation Methods and Fungal Isolatessupporting
confidence: 55%
“…El método también ha sido comprobado en inoculación de Phytophthora parasitica en cítricos (Siviero et al, 2002); así mismo, se ha documentado su uso en la inoculación de Rhizoctonia solani y Macrophomina phaseolina en melón (Cucumis melo) (Medeiros et al, 2015), con Fusarium solani y Sclerotium rolfsii en melón (Nogueira et al, 2019) y la inoculación de Diaporthe phaseolorum f. sp. meridionalis (Siviero y Menten, 1995) y Fusarium solani f. sp.…”
Section: Grupounclassified
“…Fungi of the Fusarium solani species complex cause dry rot, showing symptoms of root striae that block the vascular tissues for sap circulation, causing indirect and dry rot of the roots with coloration varying from yellow to brown (Ghini et al, 2011;Hohenfeld et al, 2018). This fungus can stay in the soil for a long because it can survive through resistance structures called chlamydospores (Nogueira et al, 2019). As it is a soil borne fungus, it is difficult to control, and there are no records of chemical products recommended for controlling the disease in cassava (Agrofit, 2024).…”
Section: Introductionmentioning
confidence: 99%